1999
DOI: 10.1111/j.1745-4530.1999.tb00470.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF FREQUENCY AND WAVE FORM ON THE ELECTRICAL CONDUCTIVITY‐TEMPERATURE PROFILES OF TURNIP TISSUE1

Abstract: Electrical conductivity (σ) – temperature (T) curves were determined as a function of frequency and wave form of alternating current. Turnip cylinders were sandwiched between titanium electrodes and heated ohmically to 100C using four frequencies (4, 10, 25 and 60 Hz) and three wave forms (square, sine and sawtooth). The σ‐T curve shifted upward at 4 Hz for all wave forms. Curses were not significantly different at 10, 25 and 60 Hz for sawtooth and sine wave forms, while those for square waves were not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 7 publications
2
24
1
1
Order By: Relevance
“…We observed that the heating rate of salsa for a 60-Hz square wave was significantly (P Ͻ 0.05) lower than for 60-Hz sine and sawtooth waves. This result was in agreement with other research studies which showed that square wave was less efficient than the sine wave at 60 Hz (14,15). These investigators mentioned that changing of the waveform affected electrical conductivity, and this effect increased as the frequency decreased (14).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We observed that the heating rate of salsa for a 60-Hz square wave was significantly (P Ͻ 0.05) lower than for 60-Hz sine and sawtooth waves. This result was in agreement with other research studies which showed that square wave was less efficient than the sine wave at 60 Hz (14,15). These investigators mentioned that changing of the waveform affected electrical conductivity, and this effect increased as the frequency decreased (14).…”
Section: Discussionsupporting
confidence: 83%
“…This result was in agreement with other research studies which showed that square wave was less efficient than the sine wave at 60 Hz (14,15). These investigators mentioned that changing of the waveform affected electrical conductivity, and this effect increased as the frequency decreased (14). For this reason, no significant (P Ͼ 0.05) difference in the ohmic heating rate between waveforms was observed as frequency increased above 500 Hz.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Two Titanium wires, 5 mm long and 3 mm in diameter coated with 50 g of Platinum/m 2 (Magneto Special Anodes, NL) were placed in either side of this cavity and used as electrodes. Previous work has shown that metals, such as stainless steel, used as electrodes, cause electrolysis effects [18]. At 50 Hz, the Ti-Pt materials have no significant electrocatalytic properties towards foods [19].…”
Section: Experimental Cellmentioning
confidence: 99%